2021 Guidelines for Purchasing and Using Commercial Natural Enemies and Biopesticides in North America - Norman Leppla; Lynn M. LeBeck (EDIS)
This 14-page guide written by Lynn M. LeBeck and Norman C. Leppla and published by the UF/IFAS Entomology and Nematology Department provides assistance in selecting, purchasing and using commercially available natural enemies and biopesticides for managing accurately diagnosed pest problems.